Time to treat the climate and nature crisis as one indivisible global health emergency - Abbasi, Kamran; Ali, Parveen; Barbour, Virginia; Benfield, Thomas; Bibbins-Domingo, Kirsten; Hancocks, Stephen; Horton, Richard; Laybourn-Langton, Laurie; Mash, Robert; Sahni, Peush; Sharief, Wadeia Mohammad; Yonga, Paul; Zielinski, Chris (Journal of Current Health Sciences, 2023)
Over 200 health journals call on the United Nations, political leaders, and health professionals to recognise that climate change and biodiversity loss are one indivisible crisis and must be tackled together to preserve health and avoid catastrophe. This overall environmental crisis is now so severe as to be a global health emergency.